Flaws in Anticoagulation Strategies in Patients With Atrial Fibrillation at Hospital Discharge. (May 2019) - Kartas, Anastasios; Samaras, Athanasios; Vasdeki, Dimitra; Dividis, George; Fotos, George; Paschou, Eleni; Forozidou, Evropi; Tsoukra, Paraskevi; Kotsi, Eleni; Goulas, Ioannis; Efthimiadis, George; Karvounis, Haralambos; et al.
Background: Proper anticoagulation is a crucial therapeutic regimen in atrial fibrillation (AF). Objectives: To evaluate the real-life anticoagulation prescriptions of AF patients upon hospital discharge. Methods: We studied 768 patients with comorbid AF who were discharged from the cardiology ward of a tertiary hospital. We assessed the appropriateness of oral anticoagulation (OAC) regimens at discharge based on stroke risk (CHA2 DS2 -Vasc score), SAMe-TT2 R2 (sex, age, medical history, treatment, tobacco, race) score for vitamin K antagonists (VKA), and European labeling for nonvitamin K oral anticoagulant (NOAC) dosing. Logistic regression identified factors associated with suboptimal OAC use. Results: Of 734 patients at significant (moderate or high) stroke risk, 107 (14.6%) were not prescribed OAC, which was administered to 23 (67.6%) of 34 patients at low risk. Nonprescribing of OAC to high-risk patients was associated with paroxysmal AF (adjusted odds ratio [OR]: 2.42, 95% confidence interval [CI]: 1.47-3.99, P < .001), history of major bleeding (adjusted OR: 1.89, 95% CI: 1.03-3.47, P = .039), and concomitant antiplatelet use (adjusted OR: 5.78, 95% CI: 3.51-9.51, P < .001). Anticoagulation control was inadequate (SAMe-TT2 R2 score > 2) in 102 (50.2%) VKA-treated patients. Off-label dosing was evident in 118 (28.9%) NOAC-treated patients and was associated with a prior stroke/transient ischemic attack (adjusted OR: 2.06, 95% CI: 1.10-3.85, P = .023). Both outcomes were independently associated with low creatinine clearance. Conclusions: One of 6 patients with AF newly discharged from the hospital was treated discordantly for the corresponding risk of stroke. Suboptimal OAC use was evident in half of VKA regimens, twice as common compared to NOACs, and could be predicted by several clinical parameters.